Knowing the nurse practitioner: dominant discourses shaping our horizons - Rashotte, Judy (Nursing philosophy, 2005)
The purpose of this paper is to examine the various discourses, particularly the dominant instrumental and economic discourses that have brought the phenomena of the nurse practitioner (NP) into being. It is proposed that NPs have been constituted as an object of nature and therefore understood metaphorically as a tool or instrument within the health care system to be used efficiently and effectively. Heidegger's philosophical analysis of the question concerning technology is used to argue that our current ways of knowing the NP through these discourses, with their emphasis on calculative logic, have resulted from our modern view of the essence of technology. It is also argued that there is now a need to shape our horizons concerning the NP in new and different ways. There is a need to engage in dialogical forms of research in order to evoke the richness and depth of what it means to be an NP, that is, to reveal the other modes of expression by which we define ourselves, understand others and nursing.